1985
DOI: 10.1080/03601238509372496
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the half life of fenthion in New Zealand white rabbits using three routes of administration

Abstract: The purpose of this research was to determine if the route of administration influenced the biological half life of fenthion, an organophosphorous insecticide. Twenty mg/kg fenthion was given to groups of New Zealand White Rabbits via the oral, subcutaneous and intravenous routes respectively. The distribution of fenthion in the blood of New Zealand rabbits followed an open two compartment model. There were no significant differences in the kinetic parameters (2, beta, K12, K21, Kel) derived for the three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the case of V, the synthetic porphyrin predominantly oxidized the C-S sulfur as recently reported for aromatic and aliphatic sulfides, 30) followed by ester cleavage and desulfuration to form Vd and Ve. Although it was not clear which site, PϭS or C-S sulfur, was more susceptible to oxidation, significant amounts of oxon and its sulfone in addition to Va, Vb and Ve and hydrolytic products were detected in rat 31) and rabbit 32) metabolism studies. These results indicated that the electronic character primarily controlled the porphyrin-mediated oxidation and the absence of steric constraint caused the different reac- tion profiles from P450-catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of V, the synthetic porphyrin predominantly oxidized the C-S sulfur as recently reported for aromatic and aliphatic sulfides, 30) followed by ester cleavage and desulfuration to form Vd and Ve. Although it was not clear which site, PϭS or C-S sulfur, was more susceptible to oxidation, significant amounts of oxon and its sulfone in addition to Va, Vb and Ve and hydrolytic products were detected in rat 31) and rabbit 32) metabolism studies. These results indicated that the electronic character primarily controlled the porphyrin-mediated oxidation and the absence of steric constraint caused the different reac- tion profiles from P450-catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%